Tracing knowledge diffusion trajectories in the research field of cyberbullying - Abderahman Rejeb; Karim Rejeb; Imen Zrelli; Edit Süle (Heliyon)
In today's digital age, cyberbullying has emerged as a pervasive issue that affects individuals across various social media platforms and digital communication channels. This review explores the developmental trajectory of cyberbullying as an interdisciplinary academic field, employing a unique combination of co-word analysis and main path analysis (MPA) across a substantial body of 5183 documents. This integrated methodological approach allows for a nuanced examination of the evolution of themes and influential works within the realm of cyberbullying research. The findings highlight a complex landscape where initial focus areas, such as the behavioral and psychological triggers of cyberbullying, progressively expand towards exploring effective preventive measures and intervention strategies. Key themes identified include the impact of digital literacy, the dual role of social media as both a vector and a tool against cyberbullying, and the potential of technological advancements in detecting and mitigating cyberbullying. This comprehensive mapping and analysis deepens our understanding of cyberbullying and highlights the dynamic nature of this field, suggesting new directions for future research and practical applications to effectively address cyberbullying across various social and technological contexts. This study represents a pioneering effort in synthesizing a broad spectrum of research to offer detailed insights into the changing dynamics of cyberbullying, marking a significant contribution to both academic knowledge and practical approaches to handling cyberbullying.